Business Strategies for Sustainability-Motivated Innovation A Conceptual Framework. - Arogyaswamy, B.
Innovation has been and continues to be a key factor in the competitive advantage of business firms and economic growth of nations. However, while the creation of new offerings that are appealing to customers is central to corporate success, substantial negative outcomes may accompany or follow the unbridled pursuit of innovation. This paper investigates, among others, environmental damage and the diminution of social and political stability as problems arising from innovation and introduces a framework that may be used to enhance environmental and social sustainability through innovation. For the purposes of this study, innovation is viewed according to three types: product, process, and managerial. We also collapsed numerous sustainability strategies that have been identified in the literature into four categories: cost- and differentiation-based (environmental) and employee- versus communityoriented (social). The three innovation types are arrayed against the four sustainability strategies thereby yielding twelve approaches to innovating with sustainability in mind. Numerous examples are provided to illustrate how the framework is being or may be used. Such sustainability criteria can also serve vice-versa as drivers of organizational innovation.